2006
DOI: 10.1016/j.febslet.2006.03.018
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein facilitates the toxicity of oxidized catechol metabolites: Implications for selective neurodegeneration in Parkinson's disease

Abstract: Free radicals, including dopamine (DA)-oxidized metabolites, have long been implicated in pathogenesis of Parkinson's disease (PD). However, the relationships between such oxidative stresses and a-synuclein (a-S), a major constituent of Lewy bodies, remain unknown. In this study, we established neuronal cells that constitutively express a-S and tetracycline-regulated tyrosinase. While tyrosinase overexpression induced apoptosis, co-expression of wild type or A53T mutant human a-S with tyrosinase further exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
(50 reference statements)
6
41
0
Order By: Relevance
“…This hypothesis is corroborated by the fact that the neurotoxicity associated with aS overexpression is remarkably reduced when DA synthesis is inhibited (7), and the toxicity of oxidized catechol metabolites is exacerbated by the expression of WT aS or the PD-linked A53T variant (8). The fact that DA itself, at concentrations found in dopaminergic neurons, is not able to impair neuron functionality and cause cell death as found in PD (9) suggests that another molecule produced via DA metabolism could be responsible for this selective neuronal degeneration (10).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…This hypothesis is corroborated by the fact that the neurotoxicity associated with aS overexpression is remarkably reduced when DA synthesis is inhibited (7), and the toxicity of oxidized catechol metabolites is exacerbated by the expression of WT aS or the PD-linked A53T variant (8). The fact that DA itself, at concentrations found in dopaminergic neurons, is not able to impair neuron functionality and cause cell death as found in PD (9) suggests that another molecule produced via DA metabolism could be responsible for this selective neuronal degeneration (10).…”
supporting
confidence: 53%
“…The inhibition of mitochondrial complex I, which synthesizes NAD, a cofactor for ALDH, also results in elevated DOPAL concentration and the death of dopaminergic neurons in vitro and in vivo (11,46). Importantly, PD patients have a deficit in mitochondrial complex I (8). Given that aS is perhaps the single most critical player in the etiology of Parkinson disease, links between DOPAL and synuclein aggregation or function may be key to understanding the basis for selective dopaminergic cell death in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its electrophilic carbonyl carbon, DOPAL contains two easily oxidizable phenolic groups. Auto-oxidation of DO-PAL to the DOPAL-o-quinone, a process reported for dopamine (Hasegawa et al, 2006), may also produce free hydroxyl radicals in the presence of H 2 O 2 , similar to that reported for the dopamine derivative, 6-hydroxydopamine (Cohen and Heikkila, 1974). Furthermore, it was suggested that the ability of DOPAL to produce the hydroxyl radical may be due to its lower redox potential in relation to DOPEGAL or other dopamine metabolites (Cohen and Heikkila, 1974;Liu and Mori, 1993).…”
Section: Free Radical Generationmentioning
confidence: 55%
“…␣-Synuclein also catalyzes the formation of H 2 O 2 (Turnbull et al, 2001), which could contribute to the production of DOPAL-generated free hydroxyl radicals and subsequent aggregation of ␣-synuclein into Lewy bodies . Recently, it has been demonstrated that ␣-synuclein and oxidized catechol metabolites may work synergistically to potentiate each other's toxic effects (Hasegawa et al, 2006). ␣-Synuclein was shown to exacerbate apoptotic cell death induced by o-quinone metabolites of dopamine and L-dopa, and it was suggested that oxidized catechol metabolites may form adducts with ␣-synuclein, leading to enhanced aggregation.…”
Section: F Potential Role In Neurodegenerationmentioning
confidence: 99%
“…DOI 10.1002/em cells and neural function [Picada et al, 2003a,b;Hasegawa et al, 2006]. The cytotoxic effects of APO on cultured neurons has been shown to be associated with its auto-oxidation products.…”
Section: Catechol and Dna Damage: An Oxidative Pathwaymentioning
confidence: 98%